Transient Seasonal and Chronic Poverty of Peasants : evidence from Rwanda - Muller, Christophe; Centre for the Study of African Economies (Oxford CSAE Publishing, Institute of Economics and Statistics, University of Oxford, 1997)
Using panel data from Rwanda, the paper estimate seasonal transient and chronic poverty indices, for different poverty line, poverty indicators, equivalence scale, and with and without the corrections for price variability and for the sampling scheme. The author also estimated sampling standard errors for the poverty indices. The worse poverty crises occur after the dry season at the end of the year.
"April 1997."
Includes bibliographic references (p. 53-56).
osc 28/7/16
Loans
Keywords: Poverty --- Statistics; Rural poor; Peasants -- Economic conditions; Seasonal variations (Economics); Labor mobility; Seasonal labor; Rwanda